The Effect of technical innovation on the human resources management ambidexterity through job emededdness - jabbar, Duaa mohammed; Mohammed, Atheer Abdullah (Journal of Economics and Administrative Sciences, 2021)
The current research aims to validate the Effect of technical innovation on human resources management ambidexterity through job embeddedness. The current research was done in Al-Etihad Food Industries Co. Ltd. And within the industrial environment, the research was designed according to the descriptive research. And to achieve the main goal of the research above, the researcher used the questionnaire as a key instrument to collect data through the views of a sample of managers, and employees at the senior, middle and executive management level. The research sample reached (107) individuals, the data were analysed using the statistical packages (SPSS v. 26) and ( SMART PLS v 3. 3. 8) the group of statistical methods ( bazonic media, normative deviation, difference factor, environmental adequacy test, corrosive analysis, materiality, porson, simple linear decline, Sobel news) was employed to extract results. The research reached a set of conclusions, the most notable of which was that Al-Etihad Food Industries Co. Ltd. Company demonstrated its ability to guide the human resources management ambidexterity in improving its technical innovation directly, and indirectly using job embeddedness, especially as it relies on links and sacrifice when it attempts to raise high levels of such creativity. It may be appropriate when it wants to reduce the level of technical innovation. While the scientific impact of research was to verify the relationship of promoting technical innovation under the human resources management ambidexterity by streamlining functional lines, the current study represents adding a small part of knowledge and is a starting point for much future research and resolving the problems that industrial organizations may face in the future through the recommendations to be formulated, in addition to the need for such studies by Iraqi industrial organizations, especially the light of current trends focusing on how to develop our national products